The cooperative script base concrete media on biology higher order thinking and interpersonal communication skills - Nukhbatul Bidayati Haka; Intan Agustin; Bambang Sri Anggoro (JPBIO (Jurnal Pendidikan Biologi), 2020)
The success of student achievement in the formation of HOTS and interpersonal communication skills is by applying an appropriate learning model, one of which is the cooperative script learning model. This research aims to determine how the influence of the cooperative script model aided by concrete media in studying plant tissue material on HOTS and interpersonal communication skills. Quasi-experimental design research methods. The population was all students of class XI SMA Negeri 15 Bandar Lampung, amounting to 162 students, the research sample contained two classes, namely the experimental class and the control class totaling 31 students each. The data analysis of the pretest and posttest using the MANOVA test analysis. The results showed that the application of the cooperative script model helped by concrete media affected HOTS and biology students interpersonal communication. Can be seen from the value significant was 0.000<0.05 then H0 is rejected and H1 is accepted. The results of Manova Test on HOTS and interpersonal communication shows the value significant was 0.000<0.05 so that H0 is rejected, it means learning activities using cooperative script learning models assisted by concrete media affect HOTS and biology students interpersonal communication skills.Keywords: Cooperative script, higher order thinking skills, interpersonal communication, concrete media